Effect of Co on the phase stability of CrMnFeCoxNi high entropy alloys following long-duration exposures at intermediate temperatures. (November 2019) - Bloomfield, M.E.; Christofidou, K.A.; Jones, N.G.
Abstract: The effect of Co on the phase stability of the CrMnFeCox Ni family of alloys, where the atomic ratio x = 0, 0.5, 1.5, has been experimentally established following 1000 h heat treatments at 900 and 700 °C and up to 5000 h at 500 °C. All the alloys were single phase fcc in the homogenised condition, except for CrMnFeNi which also contained bcc precipitates that remained present following exposures at 900 °C and 700 °C. The exposures at 900 °C and 700 °C also resulted in the formation of σ phase precipitates in the CrMnFeNi and CrMnFeCo0.5 Ni alloys but not in the CrMnFeCo1.5 Ni alloy. These data, in conjunction with results previously published in the literature, conclusively establish that Co stabilises the fcc matrix at elevated temperatures. However, at 500 °C, further bulk decomposition in the CrMnFeNi alloy was observed, consisting of a fine-scale intergrowth of a NiMn L10 phase and CrFe σ phase. Grain boundary precipitates were also observed following exposure at 500 °C in the CrMnFeCo0.5 Ni and CrMnFeCo1.5 Ni alloys. Four different phases were observed on the grain boundaries of the CrMnFeCo0.5 Ni alloy (Cr carbide, σ, FeCo B2 and NiMn L10 ), whilst only two phases were found on the grain boundaries of the CrMnFeCo1.5 Ni alloy (Cr carbide and NiMn L10 ). The experimental observations facilitated an assessment of the fidelity of current thermodynamic predictions of phase equilibria. All the phases predicted were observed experimentally and the σ stability fitted the experimental observations well. However, at lower temperatures, thermodynamic predictions were less consistent with experimental observations, underpredicting the extent of the B2 phase field and failing to predict the formation of the L10 phase. Graphical abstract: Image 1 Highlights: Co stabilises fcc solid solution relative to σ and bcc phases at 700 & 900 °C. All alloys decompose into multiple intermetallic phases when exposed at 500 °C. NiMn L10, FeCo B2, Cr carbide & σ all identified following 500 °C exposures. Fidelity of TCHEA3 predictions questionable, particularly at lower temperatures.